Relationship between serum uric acid and mortality among hemodialysis patients: Retrospective analysis of Korean end-stage renal disease registry data - Chang Seong Kim; Dong-Chan Jin; Young Cheol Yun; Eun Hui Bae; Seong Kwon Ma; Soo Wan Kim (The Korean Society of Nephrology, 2017)
Background: It is thought that hyperuricemia might lower the risk of mortality among hemodialysis patients, unlike in the general population, but the evidence is controversial. The aim of the current study was to evaluate the impact of serum uric acid level on the long-term clinical outcomes of hemodialysis patients in Korea. Methods: Retrospective analysis was performed on data from the End-Stage Renal Disease Registry of the Korean Society of Nephrology. This included data for 7,333 patients (mean age, 61 ± 14 years; 61% male) who received hemodialysis from January 2001 through April 2015. Initial laboratory data were used in the analysis. Results: The mean serum uric acid level in this study was 7.1 ± 1.7 mg/dL. Body mass index, normalized protein catabolic rate, albumin, and cholesterol were positively correlated with serum uric acid level after controlling for age and sex. After controlling for demographic data, comorbidities, and residual renal function, a higher uric acid level was independently associated with a significantly lower all-cause mortality (hazard ratio [HR], 0.90 per 1 mg/dL increase in uric acid level; 95% confidence interval [CI], 0.83-0.97; P = 0.008), but not cardiovascular mortality (HR, 0.90; 95% CI, 0.80-1.01; P = 0.078). Comparing uric acid levels in the highest and lowest quintiles, the HR for all-cause mortality was 0.65 (95% CI, 0.42-0.99; P = 0.046). Conclusion: Hyperuricemia was strongly associated with a lower risk of all-cause mortality, but there seems to be no significant association between serum uric acid level and cardiovascular mortality among Korean hemodialysis patients with end-stage renal disease.